Digital Transformation: An Overview of the Current State of the Art of Research. (September 2021) - Kraus, Sascha; Jones, Paul; Kailer, Norbert; Weinmann, Alexandra; Chaparro-Banegas, Nuria; Roig-Tierno, Norat
The increasing digitalization of economies has highlighted the importance of digital transformation and how it can help businesses stay competitive in the market. However, disruptive changes not only occur at the company level; they also have environmental, societal, and institutional implications. This is the reason why during the past two decades the research on digital transformation has received growing attention, with a wide range of topics investigated in the literature. The following aims to provide insight regarding the current state of the literature on digital transformation (DT) by conducting a systematic literature review. An analysis of co-occurrence using the software VOSviewer was conducted to graphically visualize the literature's node network. Approached this way, the systematic literature review displays major research avenues of digital transformation that consider technology as the main driver of these changes. This paper qualitatively classifies the literature on digital business transformation into three different clusters based on technological, business, and societal impacts. Several research gaps identified in the literature on DT are proposed as futures lines of research which could provide useful insights to the government and private sectors in order to adapt to the disruptive changes found in business as a result of this phenomenon, as well as to reduce its negative impacts on society and the environment.